Sustained-release salt reservoir enables durable solid electrolyte interphases for practical micron-sized silicon composite anodes - Kui Lin; Junke Wu; Zhengguang Song; Yuling Yi; Fuxi Peng; Shiwen Wang; Zhimin Zou; Tongbin Lan; Junxiong Wu; Chunhai Jiang (Chemical Engineering Journal, 2026)

Consistent functional genes in methanogens along soil profiles in a temperate marshland - Yuling Tan; Nannan Wang; Kexin Li; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ming Yang; Wenwen Tan; Yuedong Guo; Yanyu Song; Fenghui Yuan; Xiaofeng Xu; et al. (Soil Ecology Letters, 2026)

Explainable machine learning-based study on the applicability of thermal indicators for university classrooms in summer - Luyao Wang; Fan Fei; Yan Wang; Yongwei Song; Yuling Xiao; Weidong Wu; Kunkun Zhao; Hiroatsu Fukuda (Building and Environment, 2026)

Effects of aquatic vegetation on sediment microbial communities and potential nitrogen cycling functions in a shallow lake - Sile Wen; Wangting Yang; Lan Zhou; Yuling Yang; Jinghao Jin; Bingjie Ren; Yuzhi Song; Yanan Bai; Lidong Shen (Journal of Soils and Sediments, 2026)

Normal/inverse sandwich structure series-engineered layer-dependent double-atom catalysts featuring bridge-bonded dual‑oxygen ligands for bifunctional oxygen electrocatalysis: Machine learning-based layer-rich extended exploration and constant-potential frontier orbital analysis - Renxian Qin; Yuanrui Li; Yuling Song; Qiang Zhang; Qingjun Zhou (Chemical Engineering Journal, 2026)

From importance to sensitivity: fuel consumption analysis of heavy-duty diesel vehicles - Yuling Song; Tianhao Liu; Tiezhu Li; Xiyuan Hu; Ruizhi Zhang; Haibo Chen (Transportation Research Part D: Transport and Environment, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Leaching and migration behavior of EICP stabilized Zn2+ -contaminated soil under extreme acid rain conditions using range analysis: Insights from soil column experiments - Yu Song; Guohuan Chen; Chennan Huang; Xiqing Li; Junjie Zheng; Jianwei Zhang; Yuling Chen (Journal of Environmental Chemical Engineering, 2026)

Characteristics of soil organic carbon and its stability under different vegetation types and restoration years in Hongze lake wetland, China - Yanan Bai; Haikun Wu; Huifeng Lu; Yuling Yang; Yanping Wang; Lei Dai; Yuchun Ma; Jinqi Wang; Yuzhi Song; Lidong Shen (Journal of Environmental Management, 2026)

The pulse of ancient fires: Reconstructing Toarcian wildfire regimes from fossil charcoals in northwest China - Yuling Na; Xiao Shi; Chi Tian; Wenpei Pei; Qianqian Song; Shaoting Tian; Bing Wang; Yan Liu; Leon Nahuel Torres; Jianxin Yu (Review of Palaeobotany and Palynology, 2026)

Shoot apical meristem-dependent adventitious bud induction from embryo axes of castor bean (Ricinus communis L.) via optimized cytokinin-auxin ratio - Liang Bai; Liying Shan; Jian Song; Mengchen Xu; Yue Wang; Ruiyan Guo; Yanli Jin; Yangguang Duan; Yuling Zhang; Zhimin Jiang; Jilong Zhong; Yan Cheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Characteristics of sediment microbial community structure under different vegetation types with various restoration durations in Hongze Lake - Yuhan Jin; Wangting Yang; Yuling Yang; Yanping Wang; Huaiping Ling; Sile Wen; Bingjie Ren; Xiuling Zhang; Zhenfa Su; Jinghao Jin; Yuzhi Song; Lidong Shen (Journal of Environmental Management, 2026)

Multistimuli-responsive degradable metal-organic framework nanoplatform potentiates photoimmunotherapy for hepatocellular carcinoma via cGAS-STING pathway activation - Yahui Wu; Zhipu Liu; Yi Zhang; Senfeng Zhao; Miaoqing Li; Ruiyang Zhang; Jiahui Cao; Peng Liu; Liming Song; Yin Liu; Yunpeng Zhai; Weijie Wang; et al. (Chemical Engineering Journal, 2026)

Preparation of omniphobic membrane by anchoring hydrophobic islands at fixed-points for treating hypersaline wastewater - Ronghua Ma; Xiaolong Lu; Jie Gu; Kai Ren; Yuling Ren; Yuefei Song; Zhong Ma (Desalination, 2025)

Trophic status impacts the potential significance of anaerobic methane oxidation driven by multiple electron acceptors in Lake Taihu sediments - Wangting Yang; Qinan Hu; Hechen Huang; Jinghao Jin; Bingjie Ren; Sile Wen; Yuling Yang; Yefan He; Yanping Wang; Yanan Bai; Yuzhi Song; Lidong Shen (CATENA, 2025)

Elemental composition of non-nest soil, nest soil, and ant bodies in globally invasive ant species Solenopsis invicta and Tapinoma melanocephalum across various habitats - Yuling Liang; Mingrong Liang; Yunbo Song; Jingxin Hong; Huimei Chen; Syed Arif Hussain Rizvi; Yongyue Lu (Science of The Total Environment, 2025)

Silica aerogel composites with excellent thermal insulation for building applications - Song He; Hongcheng Li; Yuling Zhang; Hongliang Sheng; Yajun Huang (Energy and Buildings, 2025)

Microplastics and gynecological tumors: An emerging environmental health concern - Yuling HU; Zhihui SONG; Jingwen LI; Feiyi YANG; Ling LI (Reproductive Toxicology, 2025)

Novel insights into the morphological effects of trace organic contaminants on water/PhAC selectivity in nanofiltration of sewage - Junhao Zhao; Yanan Wang; Zuqiong Jiang; Yuefei Song; Nan Deng; Yuling Ren; Ronghua Ma; Kai Jiang (Journal of Hazardous Materials, 2025)

Classification and identification of chicken-derived adulteration in pork patties: A multi-dimensional quality profile and machine learning-based approach - Hui Lu; Cong Yao; Lin An; Aiying Song; Feng Ling; Qiliang Huang; Yuling Cai; Yunguo Liu; Dacheng Kang (Food Control, 2025)

TAT-T407 Mitigates Apoptosis and Cognitive Impairments Following Cerebral Ischemia Through Disruption of TRPV1-CDK5 Interaction - Qian Feng; Ying Li; Xiangru Wen; Hui Li; Chengyu Qi; Nan Wang; Guang Zhu; Yanyan Fu; Changdong Liu; Dan Liu; Zhen Zhang; Fan Yang; et al. (Molecular Neurobiology, 2025)

Study on water temperature variation trend and disturbance patterns in hydropower development section of the upper Yellow River - Chenxu Zhao; Yuling Liu; Ce Song; Zixuan Yan (Ecohydrology & Hydrobiology, 2025)

Evaluation of the freshness (TVB-N) of pork patty during storage based on PLS-DA, SVM and BP-ANN models - Hui Lu; Aiying Song; Ming Li; Xianqi Yao; Yuling Cai; Longlong Dong; Dacheng Kang; Yunguo Liu (Food Control, 2025)

Influences of natural organic acids on the degradation of atrazine in water by pyrite-mediated Fenton oxidation - Yuling Zheng; Fang Li; Chen Yan; Wei Yang; Jia Wen; Biao Song (Journal of Water Process Engineering, 2025)

Fabrication and characterization of lysozyme fibrils/Zein complexes for resveratrol encapsulation: Improving stability, antioxidant and antibacterial activities - Min Huang; Yuling Song; Han Wang; Hao Li; Rongmi Zhou; Qing Cao; Lijuan Dong; Gerui Ren; Di Wu; Qunfang Lei; Wenjun Fang; Dan Deng; et al. (Food Chemistry, 2025)

Fabrication and characterizations of biodegradable films based on polysaccharide from Pyropia yezoensis waste with antioxidant and antibacterial activities - Xi Qiang; Yuling Song; Jianfeng Niu; Wenhui Gu; Xulei Wang; Songcui Wu; Yuhong Zhang; Lijun Wang; Guangce Wang (Journal of Applied Phycology, 2025)

Nuclear factor NF-YA4a regulates salt stress tolerance and juvenile-adult phase transition in Pyrus - Yingjie Yang; Yuling Mei; Xueping Li; Ran Wang; Chunhui Ma; Jiankun Song; Zhenhua Cui; Jianlong Liu; Xiaozhi Zhou; Dingli Li (Horticulture, Environment, and Biotechnology, 2025)

Study on the physical properties of red clay cured by different external admixtures combined with enzyme induced carbonate precipitation technology - Yu Song; Yuling Chen; Jichun Cheng; Wei Liu; Jiaqi Li; Jianwei Zhang; Junjie Zheng (Carbonates and Evaporites, 2024)

Determining optimal nitrogen concentration intervals throughout lettuce growth using fluorescence parameters - Peizhe Li; Zhangtong Sun; Yongxia Yang; Miao Lu; Huimin Li; Haoran Yan; Jin Hu; Yuling Song (Computers and Electronics in Agriculture, 2024)

Comparative analysis of anaerobic degumming effects on different bast fibers from the angle of enzyme activity and microbial community structure - Yiting Qin; Xuehui Xie; Haonan Mo; Yuling Li; Xiaoguang Chen; Yanxue Ma; Zhuoyu Zhao; Hangmi Zheng; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; et al. (Journal of Cleaner Production, 2024)

Design, construction and evaluation of collaborative bio-system of Vibrio fluvialis with Chlorella sorokiniana for treating actual printing and dyeing wastewater - Yuling Song; Lijun Wang; Xi Qiang; Menglin Guo; Wenhui Gu; Songcui Wu; Shan Gao; Xuehua Liu; Xiujun Xie; Quancheng Fan; Jing Zhang; Zengling Ma; et al. (Chemical Engineering Journal, 2024)

The shifting pattern of CO2 source sink in a subtropical urbanizing lightly eutrophic lake - Rongjie Yang; Huixing Song; Qiao Qin; Yingying Chen; Di Li; Yuling Qiu; Kezhu Lu; Yike Tan; Qingqing Chen; Xinhao Cao; Shiliang Liu (Science of The Total Environment, 2024)

Design, construction and application of algae-bacteria synergistic system for treating wastewater - Weihao Li; Lijun Wang; Xi Qiang; Yuling Song; Wenhui Gu; Zengling Ma; Guangce Wang (Journal of Environmental Management, 2024)

Fungi and bacteria trade-off mediates drought-induced reduction in wood decomposition - Shuxian Jia; Tengfeng Yuan; Yuling Fu; Josep Penuelas; Guiyao Zhou; Lingyan Zhou; Dingqin Liu; Yanghui He; Ruiqiang Liu; Xinxin Wang; Bingqian Song; Zheng Jiang; et al. (CATENA, 2024)

Responses of rice qualities to temperature and light in three different ecological environments in karst regions - Yuling Xia; Jianquan Qin; Ruike Huang; Fan Feng; Quanzhi Zhao; Xiaoyan Song (Journal of Cereal Science, 2024)

Eliminating adverse effects of fouling layer using composite membranes with dense surface layers for sustainable membrane distillation of high-strength wastewater - Peizhi Wang; Jiawei Cheng; Jinxin Yao; Yuling Ma; Chuandong Wu; Dan Song; Wei Cheng; Jun Ma; Wei Wang (Desalination, 2024)

Vertical and temporal variations in activity, abundance, and composition of nitrite-driven anaerobic methanotrophs in a paddy field - Caiyu Geng; Lidong Shen; Bingjie Ren; Hechen Huang; Jinghao Jin; Wangting Yang; Evgenios Agathokleous; Jiaqi Liu; Yuling Yang; Yanan Bai; Yuzhi Song (Applied Soil Ecology, 2024)

Plowing drag-adaptive operation control method based on motor temperature compensation for electric tractor - Qi Wang; Xudong Wang; Wei Wang; Yongjie Cui; Yuling Song (Journal of Terramechanics, 2024)

Variations of activity and community structure of nitrite-driven anaerobic methanotrophs in soils between native and invasive species in China's coastal wetlands - Jiaqi Liu; Weiqi Wang; Lidong Shen; Yanan Bai; Wangting Yang; Yuling Yang; Jiangbing Xu; Maohui Tian; Xin Liu; Jinghao Jin; Yuzhi Song (European Journal of Soil Biology, 2024)

Association of short-term PM2.5 exposure with airway innate immune response, microbiota and metabolism alterations in human airways - Shuaiqi Zhao; Huijun Li; Fuyun Yang; Yishu Yang; Yuling Zeng; Zhen An; Juan Li; Hui Wu; Jie Song; Weidong Wu (Environmental Pollution, 2024)

Drought-induced changes in rare microbial community promoted contribution of microbial necromass C to SOC in a subtropical forest - Xinxin Wang; Lingyan Zhou; Yuling Fu; Zheng Jiang; Shuxian Jia; Bingqian Song; Dingqin Liu; Xuhui Zhou (Soil Biology and Biochemistry, 2024)

Nanozyme-mediated biocatalysis as a mitochondrial oxidative stress amplifier for tumor nanocatalytic immunotherapy - Junya Lu; Luming Song; Shuaipeng Feng; Kaili Wang; Yuling Mao; Yikun Gao; Qinfu Zhao; Siling Wang (Chemical Engineering Journal, 2024)

Joint control method based on speed and slip rate switching in plowing operation of wheeled electric tractor equipped with sliding battery pack - Qi Wang; Xudong Wang; Wei Wang; Yuling Song; Yongjie Cui (Computers and Electronics in Agriculture, 2023)

An overview of biological mechanisms and strategies for treating wastewater from printing and dyeing processes - Yuling Song; Lijun Wang; Xi Qiang; Wenhui Gu; Zengling Ma; Guangce Wang (Journal of Water Process Engineering, 2023)

Manipulating polysulfide catalytic conversion through edge site construction, hybrid phase engineering, and Se anion substitution for kinetics-enhanced lithium-sulfur battery - Tong Li; Zhouhao Wang; Junping Hu; Haobin Song; Yuling Shi; Yu Jiang; Daohong Zhang; Shaozhuan Huang (Chemical Engineering Journal, 2023)

Responses of soil carbon cycling microbial functional genes to nitrogen and phosphorus addition in saline-sodic soils - Xuejun Du; Yanning Ge; Yun Zhang; Hao Hu; Yiying Zhang; Ziye Yang; Xueqin Ren; Shuwen Hu; Haojie Feng; Yuling Song (Plant and Soil, 2023)

Microbubbles preparation by partial vaporization of low boiling condensate for crude oil/water separation - Ce Wang; Yuling Lü; Chao Song; Jiakai Shi; Peng Zhang; Limin He (Journal of Water Process Engineering, 2023)

The effect of chlorfenapyr exposure on Solenopsis invicta Buren (Hymenoptera: Formicidae) - Yuling Liang; Mingrong Liang; Panpan Li; Yunbo Song; Yongyue Lu (Journal of Asia-Pacific Entomology, 2023)

The miR156x + p/SPL13-6 module responds to ABA, IAA, and ethylene, and SPL13-6 participates in the juvenile–adult phase transition in Pyrus - Minyan Song; Anqi Li; Lei Sun; Yuling Mei; Zhiyan Wang; Rihong Wang; Ran Wang; Dingli Li; Jiankun Song; Chunxiang Zhang; Yingjie Yang (Horticulture, Environment, and Biotechnology, 2023)

Plant growth strategy determines the magnitude and direction of drought‐induced changes in root exudates in subtropical forests - Zheng Jiang; Yuling Fu; Lingyan Zhou; Yanghui He; Guiyao Zhou; Peter Dietrich; Jilan Long; Xinxin Wang; Shuxian Jia; Yuhuang Ji; Zhen Jia; Bingqian Song; et al. (Global Change Biology, 2023)
Root exudates are an important pathway for plant–microbial interactions and are highly sensitive to climate change. However, how extreme drought affects root exudates and the main components, as well as species‐specific differences in response magnitude and direction, are poorly understood. In this study, root exudation rates of total carbon (C) and its components (e.g., sugar, organic acid, and amino acid) were measured under the control and extreme drought treatments (i.e., 70% throughfall reduction) by in situ collection of four tree species with different growth rates in a subtropical forest. We also quantified soil properties, root morphological traits, and mycorrhizal infection rates to examine the driving factors underlying variations in root exudation. Our results showed that extreme drought significantly decreased root exudation rates of total C, sugar, and amino acid by 17.8%, 30.8%, and 35.0%, respectively, but increased root exudation rate of organic acid by 38.6%, which were largely associated with drought‐induced changes in tree growth rates, root morphological traits, and mycorrhizal infection rates. Specifically, trees with relatively high growth rates were more responsive to drought for root exudation rates compared with those with relatively low growth rates, which were closely related to root morphological traits and mycorrhizal infection rates. These findings highlight the importance of plant growth strategy in mediating drought‐induced changes in root exudation rates. The coordinations among root exudation rates, root morphological traits, and mycorrhizal symbioses in response to drought could be incorporated into land surface models to improve the prediction of climate change impacts on rhizosphere C dynamics in forest ecosystems.

Ameliorative effect of calcium poly(aspartic acid) (PASP-Ca) and calcium poly-γ-glutamic acid (γ-PGA-Ca) on soil acidity in different horizons - Fei Kang; Qilin Lv; Jingbiao Fan; Yun Zhang; Yuling Song; Xueqin Ren; Shuwen Hu (Environmental Science and Pollution Research, 2023)

Fungicide exposure accelerated horizontal transfer of antibiotic resistance genes via plasmid-mediated conjugation - Houpu Zhang; Jiajin Song; Zhiruo Zheng; Tongxin Li; Nan Shi; Yuling Han; Luqing Zhang; Yunlong Yu; Hua Fang (Water Research, 2023)

Premature mortality attributable to NO2 exposure in cities and the role of built environment: A global analysis - Jian Song; Yuling Wang; Qin Zhang; Wei Qin; Rubing Pan; Weizhuo Yi; Zhiwei Xu; Jian Cheng; Hong Su (Science of The Total Environment, 2023)

Large-scale metabolome analysis reveals dynamic changes of metabolites during foxtail millet grain filling - Tao Wang; Lu Xing; Hui Song; Yangyang Wei; Pengtao Li; Quanwei Lu; Nan Hu; Yuling Liu; Yongqing Zhao; Jinrong Liu; Baohong Zhang; Renhai Peng (Food Research International, 2023)

Immobilizing arsenic in soil via amine metal complex: a case study using iron-ethylenediamine - Qilin Lv; Tairan Zhou; Tianhao Wang; Shuhan Wang; Yanning Ge; Yuling Song; Xueqin Ren; Shuwen Hu (Environmental Science and Pollution Research, 2023)

The increased medical burden associated with frailty is partly attributable to household solid fuel: A nationwide prospective study of middle-aged and older people in China - Xiaoyu Jin; Yuling Wang; Yudong Wu; Yunfeng Liang; Yuxuan Li; Xiaoni Sun; Shuangshuang Yan; Lu Mei; Junwen Tao; Jian Song; Rubing Pan; Weizhuo Yi; et al. (Science of The Total Environment, 2023)

Interaction mechanism between zein and β-lactoglobulin: Insights from multi-spectroscopy and molecular dynamics simulation methods - Chengzhi Liu; Nan Lv; Yuling Song; Lijuan Dong; Min Huang; Qing Shen; Gerui Ren; Ruibo Wu; Binju Wang; Zexing Cao; Hujun Xie (Food Hydrocolloids, 2023)

Comparing the indigenous microorganism system in typical petroleum-contaminated groundwater - Jili Wang; Yuling Zhang; Yang Ding; Hewei Song; Ting Liu; Yi Zhang; Weiqing Xu; Yujia Shi (Chemosphere, 2023)

Biomass-derived polyphosphazene toward simultaneously enhancing the flame retardancy and mechanical properties of epoxy resins - Yuling Xiao; Xiaowei Mu; Siqi Chen; Guangyong Jiang; Zhoumei Xu; Chao Ma; Lei Song; Yuan Hu (Chemosphere, 2023)

Photocatalytic degradation effect and mechanism of Karenia mikimotoi by non-noble metal modified TiO2 loading onto copper metal organic framework (SNP-TiO2@Cu-MOF) under visible light - Lijun Hu; Junfeng Chen; Yushan Wei; Mengjiao Wang; Yuling Xu; Chao Wang; Peike Gao; Yanyan Liu; Chunchen Liu; Yuhao Song; Ning Ding; Xiaomei Liu; et al. (Journal of Hazardous Materials, 2023)

Heterogeneous interfacial photocatalysis for the inactivation of Karenia mikimotoi by Bi2O3 loaded onto a copper metal organic framework (Bi2O3@Cu-MOF) under visible light - Mengjiao Wang; Junfeng Chen; Lijun Hu; Yushan Wei; Yuling Xu; Chao Wang; Peike Gao; Yanyan Liu; Chunchen Liu; Yuhao Song; Ning Ding; Xiaomei Liu; et al. (Chemical Engineering Journal, 2023)

A novel phosphorus-, nitrogen- and sulfur-containing macromolecule flame retardant for constructing high-performance epoxy resin composites - Guangyong Jiang; Yuling Xiao; Ziyan Qian; Yuting Yang; Pengfei Jia; Lei Song; Yuan Hu; Chao Ma; Zhou Gui (Chemical Engineering Journal, 2023)

Inhibition of berberine hydrochloride on Candida albicans biofilm formation - Xiaoxue Huang; Mingyue Zheng; Yuling Yi; Anamica Patel; Zhen Song; Yan Li (Biotechnology Letters, 2020)

Osteogenic and angiogenic characterization of mandible and femur osteoblasts - Xue Yang; Jun Jiang; Ling Zhou; Song Wang; Mengjiao He; Kai Luo; Yuling Chen; Xiongcheng Xu (Journal of Molecular Histology, 2019)

The contribution of oxygen-containing functional groups to the gas-phase adsorption of volatile organic compounds with different polarities onto lignin-derived activated carbon fibers - Fanyue Meng; Min Song; Yuexing Wei; Yuling Wang (Environmental Science and Pollution Research, 2019)

Study on the velocity structure of the crust in Southwest Yunnan of the north-south seismic belt—Results from the Menghai-Gengma-Lushui deep seismic sounding profile - ShuaiJun Wang; BaoJin Liu; JianShi Zhang; BaoFeng Liu; YuLing Duan; XiangHui Song; XiaoGuo Deng; CeJun Ma; YiRan Zang (Science China Earth Sciences, 2015)